Packet Format Design and Decision Directed Tracking Methods for Filter Bank Multicarrier Systems. (16th March 2010) - Amini Amini, Peiman Peiman; Farhang-Boroujeny Farhang-Boroujeny, Behrouz Behrouz
Abstract : Packetized data transmission is commonly used in wireless communication systems. Each packet starts with a preamble which is used to synchronize the receiver with carrier frequency of the incoming signal, to find a good timing phase, and to identify the channel impulse response or to adjust a set of channel equalizer parameters. In this paper, following the same philosophy, we develop a packet format for multicarrier systems that operate based on filter banks, filter bank multicarrier (FBMC) systems. The related algorithms for carrier frequency and timing recovery as well as channel identification/equalizer adjustment and methods for carrier and timing tracking loops are proposed. The proposed ideas are evaluated and their satisfactory performance are presented through computer simulations.